Effect of Diet Energy Level on the Histological Characteristics of Testes of Indigenous Barred Cock in the Western Highlands of Cameroon - Ngoula, F.; Tadondjou , T.C.D.; Kana, J.R.; Kouam, M.; Mube, K.H.; Teguia, A. (International Journal of Poultry Science, 2019)
Background and Objective: This study was conducted to determine the effect of diet energy level on the histological traits of testes. Materials and Methods: For this purpose, ninety-six days-old barred male chicks, weighing 28.33 g in average were randomly divided into 12 groups of 8 chicks each. Three feeding programs (FP) each comprising a starter diet from day old to 12 weeks (S0: 2800 kcal kg–1, S1: 2900 kcal kg–1, S2: 3000 kcal kg–1) and a grower diet from 13-20 weeks (G0: 2900 kcal kg–1, G1: 3000 kcal kg–1, G2: 3100 kcal kg–1) were used and designated FP1, FP2 and FP3, respectively. Each of the FP was randomly distributed to 4 groups of 8 birds in a completely randomized design. At 20 and 30 weeks of age, 8 cocks from each treatment group were randomly slaughtered to determine the testes weight, the testicular shape index and the testes stereological and histological traits. Result: At 20 weeks of age, feeding programs FP0 and FP2 showed a significant increase (p